2001
DOI: 10.17016/feds.2001.46
|View full text |Cite
|
Sign up to set email alerts
|

Term Structure of Interest Rates with Regime Shifts

Abstract: We develop a term structure model where the short interest rate and the market price of risks are subject to discrete regime shifts. Empirical evidence from Efficient Method of Moments estimation provides considerable support for the regime shifts model. Standard models, which include affine specifications with up to three factors, are sharply rejected in the data. Our diagnostics show that only the regime shifts model can account for the well documented violations of the expectations hypothesis, the observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
70
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 0 publications
6
70
0
Order By: Relevance
“…A frequently observed phenomenon is that a transition between business cycle expansion and contraction usually leads to significant changes in stock returns, interest rates and other financial indices. These changes exhibit certain cyclic or periodic patterns (see Bansal and Zhou [2]). Reasonably, the dynamic changes of asset prices can be better described by models that incorporate a regime-switching component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A frequently observed phenomenon is that a transition between business cycle expansion and contraction usually leads to significant changes in stock returns, interest rates and other financial indices. These changes exhibit certain cyclic or periodic patterns (see Bansal and Zhou [2]). Reasonably, the dynamic changes of asset prices can be better described by models that incorporate a regime-switching component.…”
Section: Introductionmentioning
confidence: 99%
“…Reasonably, the dynamic changes of asset prices can be better described by models that incorporate a regime-switching component. Empirical studies have provided considerable support for including regime-switching in both equity models (Hardy [13]) and interest rate models [2], especially when long terms are under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…1 These results have motivated the recent studies of the impact of regime shifts on the entire yield curve using dynamic term structure models. A common approach, as in Naik and Lee [35], Boudoukh et al [6], Evans [20] and Bansal and Zhou [3], is to incorporate Markov-switching into the stochastic processes of the pricing kernel and/or state variables. 2 The regime-dependence introduced by these studies implies richer dynamic behavior of the market price of risk and therefore offers greater econometric flexibility for the term structure models to simultaneously account for the time series and cross-sectional properties of interest rates.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies (see, for example, [3]) have also shown that regimes are intimately related to the business cycle, suggesting a close link between the regime shift and aggregate uncertainties. 3 Hence it is most likely that the Markov regime shifts represent a systematic risk which should be priced in the term structure models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation